1992
DOI: 10.1254/jjp.59.65
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pravastatin Sodium Alone and in Combination with Cholestyramine on Hepatic, Intestinal and Adrenal Low Density Lipoprotein Receptors in Homozygous Watanabe Heritable Hyperlipidemic Rabbits

Abstract: Pravastatin sodium (pravastatin), a tissue-selective inhibitor of 3-hydroxy-3-methylglu taryl coenzyme A reductase, was administered alone (50 mg/kg) or in combination with cholestyramine, a bile acid sequestrant resin, at the level of 2% in the diet to homozygous Watanabe heritable hyper lipidemic (WHHL) rabbits for 4 weeks. The low density lipoprotein (LDL)-cholesterol levels were re duced by 29% and 56% with pravastatin alone and the combination treatment, respectively. Hepatic LDL receptor activity was inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…53 This may be mediated by a reduced assembly and secretion of very low-density lipoprotein apolipoprotein B100 21,54 as well as an enhanced turnover of hepatic LDL receptors. 20 As a consequence, a diminished hepatic secretion of very low-density lipoprotein cholesterol into and an enhanced uptake of intermediate-density lipoprotein cholesterol and LDL cholesterol from plasma into liver, intestinal or other extrahepatic 55 tissues may occur. Both the hepatic and extrahepatic mechanisms, which are believed to explain the observed reduction of plasma cholesterol levels, appear to be only secondary to the competitive inhibition of HMG-CoA reductase 52,56 and possibly an only short-lived reduction of cholesterol synthesis by HMG-CoA reductase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…53 This may be mediated by a reduced assembly and secretion of very low-density lipoprotein apolipoprotein B100 21,54 as well as an enhanced turnover of hepatic LDL receptors. 20 As a consequence, a diminished hepatic secretion of very low-density lipoprotein cholesterol into and an enhanced uptake of intermediate-density lipoprotein cholesterol and LDL cholesterol from plasma into liver, intestinal or other extrahepatic 55 tissues may occur. Both the hepatic and extrahepatic mechanisms, which are believed to explain the observed reduction of plasma cholesterol levels, appear to be only secondary to the competitive inhibition of HMG-CoA reductase 52,56 and possibly an only short-lived reduction of cholesterol synthesis by HMG-CoA reductase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The hypolipidemic effects of various drugs have been investigated with WHHL rabbits (Table 2): cholesterol synthesis inhibitors, such as HMG-CoA reductase inhibitors and squalene synthetase inhibitors; inhibitors of microsomal triglyceride transfer protein, which works in the assembly of VLDL particles in liver; anionic exchange resins, which block the enterohepatic circulation of bile acids; omega-3 fatty acids, which are a component of fish oil; fibrates, which lower serum triglyceride levels. In studies with a cholesterol synthesis inhibitor, statin, serum total cholesterol levels of WHHL rabbits were decreased dose-dependently by 10–30% compared with the control group [37, 39]. The mechanisms for the reduction in serum cholesterol levels by statins are an increase in expression of mRNA of LDL receptors in the liver [39] and, decrease in the excretion of VLDL cholesterol from the liver in cases of high-dose treatment [38].…”
Section: Translational Research On the Development Of The Lipid-lomentioning
confidence: 99%
“…In studies with a cholesterol synthesis inhibitor, statin, serum total cholesterol levels of WHHL rabbits were decreased dose-dependently by 10–30% compared with the control group [37, 39]. The mechanisms for the reduction in serum cholesterol levels by statins are an increase in expression of mRNA of LDL receptors in the liver [39] and, decrease in the excretion of VLDL cholesterol from the liver in cases of high-dose treatment [38]. The agents that inhibit squalene synthetase, another rate-limiting enzyme in cholesterol synthesis, also decreased the serum cholesterol level by similar mechanisms [51].…”
Section: Translational Research On the Development Of The Lipid-lomentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of lowering serum cholesterol by HMG-CoA reductase inhibitors is now believed to be as follows: hepatic cholesterol depletion by inhibition of cholesterol synthesis may trigger the induction of hepatic LDL receptor, resulting in the stimulation of LDL removal from the blood, and may decrease the secretion of very low density lipoprotein (VLDL) choles terol (5,7). We (8,9) and other investigators (10,11) reported that pravastatin increased hepatic LDL receptor activity in normal or Watanabe heritable hyperlipidemic (WHHL) rabbits. Kovanen et al (12) reported that when mevinolin (lovastatin), an HMG-CoA reductase inhibi tor, was administered to dogs, an increase in the number of hepatic LDL receptors rather than a reduction in cho lesterol synthetic rate in the liver was responsible for the enhanced clearance of LDL from blood.…”
mentioning
confidence: 99%